Prophylactic Use of Ketamine Hydrochloride For Prevention of Post Operative Shivering (Journal of the Bangladesh Society of Anaesthesiologists, 2009)
Postoperative shivering is one of the recognized complications following general, regional anaesthesia and also effect of some surgical procedure specially in the recovery room. Shivering increases the muscular activity, O2 consumption, CO2 production and may result in hypoxaemia, hypercarbia and lactic acidosis. It is not only uncomfortable but also cold sensation which is even worse feeling than pain sensation. As a result preventing the symptoms is clearly desirable and beneficial for the patient. Different methods are suggested for prevention of postoperative shivering including biogenic monoamines, cholinomimetcis, cations, endogenous peptides, opioids, GA agents, NMDA antagonists. The present study was designed to compare the efficacy of ketamine on the patients undergoing elective surgery for prevention of postoperative shivering. The study was also done to deffect incidence of shivering, haemodynamic status, untoward effects of drug used (hallucination, unpurposeful movement, restlessness). A total number of 60 patients of ASA I and II grade of both sex, age range 30-60 yrs, weight 50-70 kg, undergoing elective gynaecological surgery was randomly selected into two groups Gr K and Gr P and received ketamine 5mg. kg-1 and placebo (normal saline) respectively at 20 minutes before the end of the operation. In the postoperative period, incidences of shivering were 80% & 50% in group "K" and "P" which are highly significant between the groups P .05. The study showed that patients of group ‘K' were less shivering with good recovery. Key words: Postoperative shivering, ketamine.   Journal of BSA, Vol. 21, No. 1, January 2008 29-35